CONTINUING PROFESSIONAL TRAINING OF PHYSICAL EDUCATION TEACHERS ON INCLUSIVE PERSPECTIVE: - Morais, Milena Pedro de; Campos, Maria João Carvalheiro; Rodrigues, Graciele Massoli (UNESP, 2020)
The process of continuing professional training in school physical education has an essential role on the inclusive perspective in order to support the teacher for the development of positive attitudes. Thus, the objective of this study was analyze the effectiveness of the training program in the levels on the Perception of Competence and Quality of Experience of 29 Physical Education teachers in process of continuous professional training, who are students of the 1st year of the Master course in Physical Education Teaching in the Basic and Secondary Cycles of the Faculty of Sport Sciences and Physical Education of the University of Coimbra, Portugal. The Self-Efficacy Scale for Inclusive Physical Education was applied, the Portuguese version of the Self-Efficacy Scale for Physical Education Teacher Education Majors towards Children with Disabilities questionnaire, at two different times, before and after performing a formative program. The results show that the participants demonstrated high levels for both the Perception of Competence and Quality of Experience after performing the training program. The research concluded that the program of continuous professional training on the inclusive perspective is an important way to be followed in order to enable the teacher to meet the diverse school demand in an inclusive context.    Received on: 19/12/2019 Reformuleted on: 20/12/2019 Accepted: 20/12/2019